Pengaruh Bahan Pelincir terhadap Sifat-Sifat Tablet Parasetamol Sistem Dispersi Padat dengan PEG 6000 - Maria Dona Octavia; Yuliana Yuliana; Auzal Halim (Jurnal Farmasi Higea, 2009)
A research has been performed on the effect of lubricant to a solid dispersion system of paracetamol tablet with polyetilenglicol 6000, the solid dispersion system of paracetamol-polyetilenglicol 6000 is prepared through the dissolution method with 7 : 3 comparison. Then physiochemical characteristics and dissolution profile evalution is ferformed to three lubricant materials, which is aerosol, stearate magnesium, and talcum.